Different position from traditional left lateral for colonoscopy? A meta-analysis and systematic review of randomized control trials - Snow Yunni Lin; Clyve Yu Leon Yaow; Cheng Han Ng; Neng Wei Wong; Hui Yu Tham; Choon Seng Chong (Chronic Diseases and Translational Medicine, 2021)
Background: Colonoscopy requires the intubation of the cecum for screening of colorectal diseases. The conventional position used for colonoscopy is the left lateral position (LLP). However, alternative positions have also been utilized to enhance the success of intubation. Thus, the aim of this study was to perform a meta-analysis of the different positions to determine the effectiveness of the individual positions for successful colonoscopy. Methods: Medline, Embase and Cochrane trials electronic databases were searched for studies on colonoscopy positions. The primary outcome was defined as the cecal intubation rate. Pooled risk ratios (RR) and 95% confidence intervals (CI) for the rates of cecal intubation were estimated. Secondary outcomes such as the cecal intubation time and adenoma detection rate were further analyzed qualitatively. Results: After reviewing 644 identified records, 7 randomized control trials (RCT) studies were included. No significant difference was observed in either comparisons, between the LLP vs. supine position (SP) (RR = 1.01, 95% CI, 0.98 to 1.04, P = 0.55) or the LLP vs. prone position (PP) (RR = 1.02, 95% CI, 0.98 to 1.06, P = 0.27). Conclusions: Amidst available literature, the use of other positions can be considered when performing colonoscopy. These further highlights that the existential practice is based predominantly on familiarity instead of evidence-based-research.